The Application of Information on the Fulfillment of Patients’ Families’ Basic Needs in the Intensive Care Unit (ICU) Waiting Room on Service Satisfaction - Rizka Ramadhani (Global Ten Public Health and Nursing Journal, 2025)
Families of ICU patients typically go through anxiety and unpredictability due to the patient’s critical condition, which generates basic needs such as information, support, proximity, comfort, and assurance. When these needs are not optimally met, family satisfaction with hospital services may decrease. Structured information delivery is expected to help families better understand the situation and increase their satisfaction. This study aimed to analyze differences in service satisfaction scores before and after the provision of information related to fulfilling the basic needs of patients’ families. The study utilized a pre-experimental pretest-posttest design with a single group, including 30 family members of ICU patients selected through purposive sampling. The independent variable involved application of information on fulfilling families’ basic needs, and service satisfaction as the dependent variable. Data were obtained through an adapted service satisfaction questionnaire based on the five SERVQUAL dimensions, with analysis performed using the Wilcoxon Signed Rank Test at a significance level of α = 0.05. Result showed higher satisfaction scores after the intervention, with a mean improvement of 2.17 points and a 13-point increase in the minimum score. The Wilcoxon test yielded p = 0.001, showing a significant variation in satisfaction scores between the pre- and post-information phases. In conclusion, structured information delivery is an effective strategy to enhance family satisfaction during the ICU waiting period, as clearer information helps families feel calmer, understand the patient’s condition, and develop a more positive perception of hospital services. These findings support the integration of structured information provision within family-centered nursing care, and hospitals are encouraged to implement routine information delivery, develop educational media, and strengthen communication to maintain family satisfaction.